Age-related changes in the gut microbiota and the core gut microbiome of healthy Thai humans - La-ongkham, Orawan; Nakphaichit, Massalin; Nakayama, Jiro; Keawsompong, Suttipun; Nitisinprasert, Sunee (3 Biotech, 2020)
The gut microbial diversity of Thai people was investigated between two large cohorts, adult and elderly subjects, from the middle region of Thailand; the cohorts were divided into different age groups of healthy adult ( 73 ) and elderly subjects ( 47 ) . The diversities of the groups were characterized using a pyrosequencing technique with primers targeting the V6–V8 region of the 16S rRNA gene, and a significant decrease in the Firmicutes and Bacteroidetes ratio from 7.3 to 4.5 was observed with increased age . The microbiota of the adult and elderly groups had a significantly higher abundance of the phylum Actinobacteria , including the three species Bifidobacterium adolescentis , Bifidobacterium longum and Bifidobacterium pseudocatenulatum , and the phylum Bacteroidetes containing the four species Bacteroides uniformis , Bacteroides ovatus , Bacteroides caccae and Bacteroides thetaiotaomicron . Firmicutes showed no significant differences between the two groups. Eleven species belonging to Firmicutes , Bacteroidetes and Proteobacteria were shared by at least 90% of all subjects and defined as core gut microbiota of healthy Thai, among which a high abundance of Escherichia coli was particularly characterized in Thai elderly individuals. Multiple linear regression analysis of age, gender, BMI and diet consumption frequency showed the correlation of age with Bacteroides and Bifidobacterium . Rice consumption frequency showed a significant positive correlation with Bacteroides , while no correlation was found for other factors. Taken together, in the gut of Thai adults, Bifidobacterium decreased and Bacteroides increased with age, while rice consumption increased the abundance of Bacteroides . These link of age and food, especially rice carbohydrate, to gut microbiota and health could be ultimately proposed as the Thai feature.